Profile and role of the teacher in inclusive hospital classrooms - Mendoza Carrasco, Mariella Victoria (2022)
Hospital classrooms are the space granted and ceded by hospitals to provide education to students - patients who are sick, interns for long or short periods; however, they have the right to continue their education in established classrooms located within a hospital. The hospital teacher is the facilitator and guide in education in multigrade hospital classrooms, where students of different ages and educational levels come to continue developing skills, abilities, capacities, and skills in an integral way, prioritizing, and working with the healthy side of the student - patient. The hospital teacher must have differentiated characteristics, to serve students in a situation of temporary or permanent special educational needs, who in turn are in a situation of vulnerability. Among the most outstanding characteristics of the profile of the hospital teacher, it can be mentioned; be innovative, creative, empathetic, assertive, have communication skills, social skills, and soft skills, which help you to have a link with each of the components of the educational and hospital community in an environment of harmony, democracy, and culture of peace. The hospital teacher must have a direct link with the students, the family, or tutors, and work in constant communication with the multidisciplinary support team of the health area, sharing recommendations and suggestions for work in the classroom, therefore, the teacher must be a flexible person and open to dialogue, with interpersonal skills that lead him to establish an assertive relationship in the classroom.